THE EFFECT OF BACK MASSAGE ON THE SLEEP QUALITY OF MENOPAUSAL MOTHERS IN THE WORKING AREA OF THE PURWADADI HEALTH CENTER, CIAMIS REGENCY IN 2024 - irianti, bayu; Indriyani, Elisa (Jurnal Ilmiah Bidan (JIB), 2025)
Background: Menopause is not having menstruation for 12 consecutive months. The standard sleep requirement for menopausal women is 7 hours/day. If a menopausal mother needs less than 7 hours of sleep / day, it can be said that the quality of sleep is not good which can cause fatigue and higher stress levels so that often menopausal women consume pharmacological drugs. One of the non-pharmacological interventions for handling the quality of sleep of menopausal women is back massage therapy. This study aims to determine the effect of giving back massage (Back Massage) on the quality of sleep of menopausal women in the Purwadadi Health Centre work area. Method: This type of research uses quasi-experiment type two group pretest and posttest design. The sampling technique used simple random sampling with a total of 90 participants. The data analysis used was univariate analysis test and non-parametric statistical bivariate test, namely Wilcoxon Signed Rank Test. Result: Wilcoxon test results obtained on back massage p-value is 0.000 meaning P < 0.05. Conclusion: Wilcoxon test results obtained on back massage p-value is 0.000 meaning P < 0.05.